Analysis of the Relationship Between Junk Food Consumption Habits and Obesity With the Results of Glucose Testing in Elementary School Students in Bengkulu City - Tedy Febriyanto; Heru Laksono; Dian Adhe Bianggo Naue (Lembaga Publikasi Ilmiah Nusantara, 2026)
The increase in obesity in children and adolescents is parallel to that of adults. Obesity is caused by an imbalance between the amount of energy taken in and that needed by the body for various biological functions such as physical growth, development, activity, and health maintenance. If this situation continues (positive energy balance) for a long time, the impact is obesity. Objective: This study aims to determine whether there is a relationship between junk food consumption habits and obesity on the results of glucose level examination. Method: The sampling technique in this study using purposive sampling method, and the sample used was many as 72 samples. Result and Discussion: The results of the study from 72 samples showed that the number of students who consumed junk food was 53% and the number of obese students was 47%. There were 13% of elementary school students with junk food consumption habits and glucose positive and the rest 87% were glucose negative. There were 11.8% of students who were obese and glucose positive, then 88.2% were glucose negative. For the chi-square analysis results, the p value was 1.000, so p > 0.05 Conclusion: Based on the results of a study of 72 samples, there was no relationship between junk food consumption habits and obesity with the results of glucose level checks in elementary school students in Bengkulu City in 2024.